A Institucionalização das práticas de sustentabilidade na Universidade Federal do Pará - MENDES, Michela Alessandra Fraga (Universidade Federal do Pará, 2018)
The purpose of this work is to understand the process of institutionalization of sustainability practices at the Federal University of Pará - Campus Belém, based on institutional theory, which presents the process of institutionalization, composed of three phases: habitualization, objectification and sedimentation.The research is methodologically structured as a kind of search qualitative, quantitative, for the processing of the data; exploratory-descriptive, about the objetives; bibliographical, documentary and as field research, as to the technical procedures. For a data collection, the instrument used in the questionnaire, structured with questions measured using the Likert scale. The proposed instrument had been applied to the servers of the University Campus of Belém. The results were analyzed and presented graphically by the Statistical Package for the Social Sciences (SPSS). The research enabled the lifting of the factors for each phase of the proposed model for analysis. The results demonstrate that the are occurring in the process of institutionalizing sustainability practices in University.